2014
DOI: 10.1016/j.jbiomech.2013.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Murine patellar tendon biomechanical properties and regional strain patterns during natural tendon-to-bone healing after acute injury

Abstract: Tendon-to-bone healing following acute injury is generally poor and often fails to restore normal tendon biomechanical properties. In recent years, the murine patellar tendon (PT) has become an important model system for studying tendon healing and repair due to its genetic tractability and accessible location within the knee. However, the mechanical properties of native murine PT, specifically the regional differences in tissue strains during loading, and the biomechanical outcomes of natural PT-to-bone heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…Boivin et al . reported the failure force of intact murine Achilles tendon to be 8.1 ± 0.6 N, and the failure force of the mouse patellar tendon is reported to be 4.73 ± 1.03 N . Measurements of failure force for intact patellar ligament and anterior cruciate ligament using our laboratory's standard methodology (unpublished work in progress) are comparable to the reported failure forces for these murine tendons and ligaments .…”
Section: Murine Rc Repair Modelsupporting
confidence: 63%
See 1 more Smart Citation
“…Boivin et al . reported the failure force of intact murine Achilles tendon to be 8.1 ± 0.6 N, and the failure force of the mouse patellar tendon is reported to be 4.73 ± 1.03 N . Measurements of failure force for intact patellar ligament and anterior cruciate ligament using our laboratory's standard methodology (unpublished work in progress) are comparable to the reported failure forces for these murine tendons and ligaments .…”
Section: Murine Rc Repair Modelsupporting
confidence: 63%
“…105 The reported failure force in the Bell et al model for intact SS tendon is, however, unusually low compared to other reported measurements for other murine tendons. 105 Boivin et al reported the failure force of intact murine Achilles tendon to be 8.1 ± 0.6 N, 129 and the failure force of the mouse patellar tendon is reported to be 4.73 ± 1.03 N. 130 Measurements of failure force for intact patellar ligament and anterior cruciate ligament using our laboratory's standard methodology (unpublished work in progress) are comparable to the reported failure forces for these murine tendons and ligaments. 129,130 Although SS tendon is not of the same size as patellar and Achilles tendons, it is unlikely that its failure force would be lower to this extent.…”
Section: Murine Rc Repair Modelsupporting
confidence: 57%
“…These readings are considerably above the failure forces of murine tendons and ligaments, including Achilles and patellar tendons, and therefore, it is improbable for a mouse to generate such a force. For example, Boivin et al reported the failure force of intact murine Achilles tendon to be 8.1 AE 0.6 N. The failure force of the mouse patellar tendon is reported to be 4.73 AE 1.03 N. 19,20 Our unpublished measurements of failure force for intact mouse patellar tendon and ACL using our standard methodology are comparable to these reported failure forces.…”
Section: Cadaveric Testingsupporting
confidence: 72%
“…Biomechanical testing was performed as previously described . Briefly, central width (48.7 ± 2.7% of full width) patella‐PT‐tibia units were dissected from each animal (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Following avulsion of tendon from the bone, natural healing, traditional surgical repair, and current tissue engineering strategies result in disorganized scar tissue that does not restore this integrated network of aligned collagen fibers embedded in mineralized fibrocartilage . Such disorganized scar tissue likely explains the increased insertion strains that persist into later stages of healing . Understanding the normal development and maturation of these structures may lead to novel insights into how to address the limitations of current repair techniques.…”
mentioning
confidence: 99%